Pengaruh Pola Asuh Orang Tua Tunggal Dalam Keluarga Terhadap Kedisiplinan Belajar Siswa - Andi Agustan Arifin; Dewi Mufidatul Ummah (JURKAM: Jurnal Konseling Andi Matappa, 2018)
The purposes of this study are to know (1) The description of foster care single parent households for students, (2) The image on students learning discipline, (3) The influence of foster care single parent households toward the students learning discipline. This study used quantitative approach with correlation design to examine the hypothesis of the influence of foster care single parent households toward the students learning discipline. There are 12 students as samples, live in single parent households or fostered by single parent. Sampling method used purposive sampling. Technique of collecting data used a closed questionnaire which was analyzed to examine the validity of its value and reliability. Verifying data of questionnaires used SPSS program Version 17,0, for windows. The results of this study showed that: (1) foster care of single parent households students is in good category, means that single parents are able to provide support or responsibility toward his son to form their characters, personalities, and to provide good values for children. (2) the level of learning discipline students is in high category, means that students have good attitude or behavior obeying the rules in school activities. (3) There is a positive influence between foster care single parent households toward the students learning discipline of SMP 1 Cina. It means that students whose parents gave good foster care will have good learning discipline.